(untitled) (Research, Society and Development, 2021)
The production of bacteriocin by Lactic Acid Bacteria has attracted great attention because of its GRAS (Generally Recognized as Safe) status, and its potential use as an additive for food preservation. The use of substrate with characteristics that provide necessary nutrients, but at a low cost, is among the essential items for the production and commercial use of bacteriocins. Therefore, the objective of this work was to evaluate the viability of the production of enterokines, using whey and corn maceration water (millhocin) as substrate in 18 and 24 hours of cultivation. Enterococcus faecium (Efm20, Efm22, Efm24, Efm25) and Enterococcus faecalis (Efs27) were characterized for the antimicrobial activity of enterocins present in the cell-free supernatant (CFS) against Listeria innocua CLIP 12612. The protein character of the antimicrobial substance was confirmed , its inhibitory activity being lost after the treatment of CFS with proteases. In contrast, the CFS antimicrobial activity remained thermostable after heat treatment (80 ° C and 100 ° C) and also when treated with catalase, which confirms that this CFS activity is not related to the action of H2O2 and lactic acid (CFS neutralized with NaOH). Counting bacterial cells (CFU / mL) of isolates grown in different media, we observed increase of CFU in MRS with substrates. The antimicrobial activity of CFS obtained from MRS media with substrate compared to MRS was similar when diffusing in agar, however, when quantifying this activity, it observed higher values of arbitrary unit for CFS obtained in MRS medium with millhocin at both times evaluated 18 and 24 hours. In conclusion, it was found that the tested substrates have great potential to be applied in the manufacture of bioconservation of food products.